Autonomy and feedback on innovative work behavior: The role of resilience as a mediating factor in Indonesian Islamic banks - Sri Suhandiah; Fendy Suhariadi; Praptini Yulianti; Ansar Abbas (Cogent Business & Management, 2023)
Autonomy, resiliency, and feedback must be prioritized for individuals in industries where behavioral innovation is required, and performance reviews of those employees should reflect this. It is difficult to do either empirical, qualitative, or conceptual research that can disclose such creative work habits in the banking business, but this research endeavors to achieve that. In order to evaluate 258 first-line managers from five regional and private Islamic banks in Indonesia, a literature-based framework has been constructed. The path model supports the idea that autonomy and resiliency foster innovative behavior at work. Resilience, autonomy, flexibility, and feedback are also significantly associated; however, feedback has not been linked to innovative work behavior. This study may be helpful to Islamic banking managers and specialists who want to learn more about innovative work behavior. While discussing this study's composition, researchers offered valuable suggestions. Implications, limitations, and prospective avenues are discussed after the research results.
Keywords: 650; autonomy; banking sector; feedback; innovative work behavior; resilience